MODEL DETERMINASI AGRESIVITAS PAJAK: ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DAN KARAKTERISTIK PERUSAHAAN PADA INDUSTRI PERBANKAN INDONESIA - BELLA PUTRIE NINDYAWAN; ARIF NADZIRUL HAQ E. (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
Tax aggressiveness in Indonesia’s banking industry has attracted growing attention amid the increasing demand for Environmental, Social, and Governance (ESG) implementation. This study aims to develop a determination model of tax aggressiveness in Indonesia’s banking sector by integrating the ESG approach with firm characteristics such as profitability, firm size, and capital structure. The research employs panel data regression analysis using secondary data from banks listed on the Indonesia Stock Exchange. The results indicate that ESG and capital structure have no significant effect on tax aggressiveness, while firm size and profitability exert a positive influence on tax aggressiveness in Indonesian banking. The adjusted R-square value of 51.57% demonstrates the model’s explanatory power in capturing variations in tax aggressiveness within the banking sector. These findings provide empirical contributions to the accounting and governance literature and serve as a basis for policy recommendations aimed at enhancing tax compliance and sustainability.